Rank-Dependent Measures of Bi-Polarization and Marginal Tax Reforms - Makdissi, Paul; Mussard, Stéphane (Université d'Ottawa | University of Ottawa, 2010)
In this paper, we investigate a dual class of bi-polarization indices, namely rank-dependent bi-polarization indices. We show that these indices may be characterized with the generalized positional transfer sensitivity property. We find necessary and sufficient conditions in order to identify bi-polarization-reducing marginal tax reforms. Precisely, we propose inverse positional dominance criteria based on the comparison of bi-polarization concentration curves. An illustration is presented using the Jordanian Household Expenditure and Income Survey 2002/2003. / Dans cet article nous analysons une classe d’indices de bi-polarisation basés sur le rang des individus dans la distribution des revenues. Nous démontrons que ces indices peuvent être caractérisés par des principes de transferts généralisés. Nous identifions une condition nécessaire et suffisante permettant d’identifier les réformes fiscales marginales permettant de réduire la bi-polarisation. La méthode est illustrée à l’aide de données du Jordanian Household Expenditure and Income Survey 2002/2003.
Keywords: Bi-polarization; Stochastic Dominance; Tax Reform; Bi-polarisation; dominance stochastique; re?formes fiscales